Murder, take two - Perry, Carol J. (Perry, Carol J. Witch City mystery, 2020)
When a recent murder bears a resemblance to a killing from almost two centuries ago, WICH-TV reporter and amateur sleuth Lee Barrett delves deeper than ever into Salem's past, and into her own psychic gifts, to catch a killer.